2022
DOI: 10.1007/s12525-022-00547-x
|View full text |Cite
|
Sign up to set email alerts
|

Business model archetypes for data marketplaces in the automotive industry

Abstract: Policymakers and analysts are heavily promoting data marketplaces to foster data trading between companies. Existing business model literature covers individually owned, multilateral data marketplaces. However, these particular types of data marketplaces hardly reach commercial exploitation. This paper develops business model archetypes for the full array of data marketplace types, ranging from private to independent ownership and from a hierarchical to a market orientation. Through exploratory interviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Instead, they need to provide analytical functionality. This assertion is supported by a finding from Bergman et al (2022) that stresses the data paradigm as solutions rather than mere "items." One concrete way is to create value by providing aggregated or standardized services.…”
Section: Data Marketplacesmentioning
confidence: 82%
See 1 more Smart Citation
“…Instead, they need to provide analytical functionality. This assertion is supported by a finding from Bergman et al (2022) that stresses the data paradigm as solutions rather than mere "items." One concrete way is to create value by providing aggregated or standardized services.…”
Section: Data Marketplacesmentioning
confidence: 82%
“…The first possible value creation archetype for a meta-platform is the discovery aggregator. According to literature, the aggregator often collects, analyzes, and offers insight from multiple data sources (e.g., Bergman et al, 2022;Garbuio & Lin, 2019). The discovery aggregator type is not focused on the role of controlling but rather on creating new connections between ecologies of platforms.…”
Section: Value Creation Archetypementioning
confidence: 99%
“…However, we observed that interviewees sometimes based their answers on (1) data-sharing platforms that purely focus on facilitating data exchange between partners; or (2) general view of data sharing without considering intermediaries like data marketplaces. This limitation is expected since interviewees are not very familiar with data marketplaces due to the diversity of data marketplaces' business models (Bergman et al, 2022;Fruhwirth et al, 2020;. Therefore, we kept an eye on this issue during the interviews and clarified the concepts to the interviewees when this issue arose.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Especially in practice, archetypal DDBMs offer a concrete strategic orientation for the transformation towards DDBMs as they systematically characterize configurations of business models (Müller and Buliga 2019). In this context, archetypes depict an aligned set of business model components that help decision-makers to develop a clearer understanding of how an aspired DDBM creates, delivers, and captures value (Pieroni et al 2020;Bergman et al 2022).…”
Section: Introductionmentioning
confidence: 99%